Social information and bandwagon behaviour in voting: An economic experiment - Ivo Bischoff; Henrik Egbert (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
We present an economic experiment on the impact of social information on voter behaviour and find strong support for bandwagon behaviour in voting decisions. In total, 418 subjects participated in the experiment. Bandwagon behaviour is found among both male and female subjects.
Keywords: C90; D72; 330; bandwagon behaviour; social information; voting motives; economic experiment; Wahlverhalten; Konsuminterdependenz; Informationsverhalten; Test